Physicochemical, rheological and functional properties of modified starches from the tubers of Plectranthus esculentus - Ursula Chinwe Kemas; Ruth E Guktur; Nelson Agaba Ochekpe; Ndidi C. Ngwuluka; Elijah Irmiya Nep (British Journal of Pharmacy, 2020)
Native starch extracted from the tubers of Plectranthus esculentus (Family: Lamiaceae) was modified by acetylation, oxidation, carboxymethylation, xerogel formation, acetylation/xerogel formation, and acetylation/oxidation. Starch syneresis, swelling power and solubility were determined by gravimetric techniques at 10% w/v of starch dispersion. Rheological properties were determined on a Bohlin Gemini HR Nano Rotonetic drive 2rheometer while the structural properties were evaluated using Fourier transform infra-red (FTIR) spectroscopy and x-ray diffractometry (XRD). FTIR confirmed the presence of acetyl groups at 1700 cm-1 and carboxymethyl groups at 1579 cm-1. The acetylated derivatives were resistant to syneresis. XRD displayed crystallized region with three prominent peaks, centred on 2θ = 15.1, 17.2and 23.2°, for the native starch, acetylated and oxidized starches while the carboxymethylated, xerogelized, and acetylated/xerogelized derivatives were typically amorphous. The derivatives (carboxymethylated andacetylated/xerogelyzed) were thermally stable and formed viscoelastic gel at room temperature. Conversely, dispersions of the native starch and the derivatives (acetylated, oxidized and acetylated/oxidized) exhibited thermal transitions due to gelatinization. The acetylated derivatives have potential in terms of shelf-life, stability, and diverse opportunities for multiple applications in pharmaceutical and food industries.